2020
DOI: 10.1007/s12646-020-00568-6
|View full text |Cite
|
Sign up to set email alerts
|

Walking in My Shoes: Imagined Synchrony Improves Attitudes Towards Out-groups

Abstract: People are prone to dividing others into the categories of ‘us’ and ‘them’. This can be particularly detrimental to minorities who may experience social exclusion, prejudice, and reduced access to equal opportunities. One method of improving intergroup relations is to create opportunities for contact. Common contact interventions have members of different groups meet and engage in conversation. There are also non-verbal embodied intergroup activities that produce the same effects. Previous work has shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Stupacher et al (2017) demonstrated that merely watching two stick figures walking in synchrony with the music and imagining being one of them can have a positive impact on feelings of closeness and affiliation toward the other stick figure. In line with these findings, participants in a non-musical study (Atherton & Cross, 2020) who imagined walking in synchrony with outgroup members exhibited increased subjective empathy and reduced negative attitudes towards these members. This evidence indicates that the processes of perceiving and actively attempting to achieve synchrony may be served by a common underlying mechanism (Prinz, 1997;Stupacher et al, 2017).…”
Section: Future Research Exploratory Avenues and Implications Of The ...supporting
confidence: 58%
See 1 more Smart Citation
“…Stupacher et al (2017) demonstrated that merely watching two stick figures walking in synchrony with the music and imagining being one of them can have a positive impact on feelings of closeness and affiliation toward the other stick figure. In line with these findings, participants in a non-musical study (Atherton & Cross, 2020) who imagined walking in synchrony with outgroup members exhibited increased subjective empathy and reduced negative attitudes towards these members. This evidence indicates that the processes of perceiving and actively attempting to achieve synchrony may be served by a common underlying mechanism (Prinz, 1997;Stupacher et al, 2017).…”
Section: Future Research Exploratory Avenues and Implications Of The ...supporting
confidence: 58%
“…Furthermore, as individuals with higher trait empathy are more susceptible to the affiliative effects of synchronous movements (Figure 1(b); Stupacher et al, 2021), adopting an empathic perspective toward co-performers (situational empathy) might also moderate those social bonding effects of synchronisation (Figure 1(c); see also Cross et al, 2012 about the role of flexibility in musical group interactions). The attained interpersonal synchronisation between co-performers increases their perceived similarity (Rabinowitch & Knafo-Noam, 2015), contributing to an increase in subjective (or situational) empathy towards one another (situation-specific changes – Figure 1(d); Atherton & Cross, 2020; Koehne et al, 2016a). The repeated practice of synchronizing and empathising with others might also have longitudinal effects, generating cumulative changes in dispositional empathy (Figure 1(e)), as observed in interventions for children (Rabinowitch et al, 2013), as well as adults (Leppma & Young, 2016).…”
Section: The Positive Feedback Loop Of Empathy and Interpersonal Sync...mentioning
confidence: 99%
“…In order to further align our findings with contemporary physical social synchrony research, future investigations may consider testing the effects of imagined synchrony with specified others. For example, recent work suggests that actual [55] and imagined coordination [49] affect relationships across group boundaries. Indeed, it is suggested that both actual and imagined coordinated walking might influence self-other perspectives even for co-actors who are members of outgroups [48].…”
Section: Plos Onementioning
confidence: 99%
“…Researchers have revealed that imagining a positive verbal interaction improves relationships between people similar to actual positive contact [43][44][45][46]. There is also evidence that imagining walking in synchrony can foster affiliation towards small groups of people one has previously met [47] and influence attitudes towards outgroup members just as physical synchrony does [48,49].…”
Section: Introductionmentioning
confidence: 99%